Ultrazvočna razpršilna piroliza materialov, na primeru TiO2 nanodelcev - Rudolf, Rebeka; Jelen, Žiga; Stopić, Srečko; Majerič, Peter (Anali PAZU, 2022)
This article presents new technological advances, trends and the latest scientific results of the bottom-up nanotechnology method called Ultrasonic Spray Pyrolysis (USP) in comparison with other similar processes. USP can produce micro and even nanoparticles from aerosol, which is generated with the use of ultrasound from a chosen solution. Review will show some latest key findings in the field of USP, with the focus of getting a new improved solution, not only in Nanotechnology, but also in a wide range of materials` synthesis, including Micro- and Metastable or Multicomponent forms to increase their transition for special application in different engineering areas in the future. The paper concludes with a presentation of the USP synthesis of TiO2 nanoparticles and their characterization.